CACHORRO DOIDO: LÓGICAS, SENTIDOS E COMPREENSÕES DA PRÁTICA DO TRÁFICO DE DROGAS E CRIMES PATRIMONIAIS NO ESTADO DO ESPIRITO SANTO - Bacellar, Gusthavo Ribeiro (2020)
Through interviews with graduates convicted of drug trafficking and property crimes in the State of Espírito Santo, we sought to analyze the elements that were common in the narrated trajectories and that, in some way, may have been related to their illeg